EXAMINING THE LEGAL COMPETENCE OF CLIENTS WITH MILD COGNITIVE IMPAIRMENT: ETHICAL RESPONSIBILITIES OF A NOTARY IN THE EXECUTION OF A DEED - Irfah Aprillia Rahma; Indratirini (Sekolah Tinggi Ilmu Hukum Awang Long, 2026)
The integrity of notarial deeds in Indonesia hinges upon the fulfillment of subjective legal requirements, principally the legal capacity to act and true consent (wilsovereenstemming), as mandated by Article 1320 of the Civil Code. This research addresses a critical contemporary challenge posed by clients diagnosed with Mild Cognitive Impairment (MCI). While MCI clients are formally considered legally competent (de jure), as they are typically not placed under formal guardianship, their functional cognitive deficits create a legal grey area, potentially invalidating the deed due to vitiated consent. This circumstance directly threatens the principle of legal certainty that notarial deeds are intended to uphold. This study employs Normative Legal Research with a Statute and Conceptual Approach, utilizing primary legal materials such as the Notary Law (UUJN) and the Civil Code, supplemented by professional ethical codes. The analysis focuses on the existing normative deficiencies in Indonesian law regarding the assessment of functional capacity beyond formal guardianship status. The conclusion highlights a significant demand for the expanded implementation of the Ethical Due Diligence Principle by notaries. This ethical responsibility must transcend minimum legal requirements. To protect vulnerable clients and minimize the risk of deed cancellation, notaries must adopt a Defensive-Protective Procedural Model. Key elements of this model include: 1) Developing robust, non-medical observation skills to detect MCI indicators; 2) Utilizing external verification mechanisms, such as requesting functional capacity certificates from medical specialists; and 3) Documenting every ethical precaution within the deed itself as a crucial defensive measure against future legal claims. This ethical expansion is necessary to safeguard both the client's interests and the integrity of the notarial profession.